2002
DOI: 10.1046/j.1440-1681.2002.03707.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence For The Existence Of A Constitutive Nitric Oxide Synthase In Vascular Smooth Muscle

Abstract: 1. We have identified a neuronal nitric oxide synthase (NOS)-like constitutive form of NOS in vascular smooth muscle (VSM) using a functional contractility approach as well as immunohistochemical methods. 2. N(G)-Nitro-L-arginine methyl ester, N(G)-monomethyl-L- arginine and N(G)-nitro-L-arginine (L-NOARG), the competitive inhibitors of NOS, inhibited Mg(2+)-induced relaxation of de-endothelialized rat aorta precontracted with phenylephrine (PE). This Mg(2+) relaxation of VSM was not affected by inhibitors of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 3 publications
1
13
0
Order By: Relevance
“…This suggests that NO responsible for the tachyphylaxis in EÀ rings is likely produced by a constitutive nNOS present in vascular smooth muscle cells. Our results confirm the study of Cheah et al (2002), which demonstrated a constitutive neuronal isoform of NOS present in vascular smooth muscle cells of Sprague-Dawley rats.…”
Section: Discussionsupporting
confidence: 91%
“…This suggests that NO responsible for the tachyphylaxis in EÀ rings is likely produced by a constitutive nNOS present in vascular smooth muscle cells. Our results confirm the study of Cheah et al (2002), which demonstrated a constitutive neuronal isoform of NOS present in vascular smooth muscle cells of Sprague-Dawley rats.…”
Section: Discussionsupporting
confidence: 91%
“…In blocking the production of NO from skeletal muscle, both endothelial cell and/or vascular smooth muscle cell production would also be blocked. The ability of endothelial cells to produce NO is well documented, and there is evidence that vascular smooth muscle cells contain NOS (9,10,12) and are capable of producing NO (10), although the purpose of this autocrine process is not well understood.…”
Section: Vasodilators Implicated In the Dilatory Response To Muscle Cmentioning
confidence: 99%
“…However, because the experiments were carried out in the presence of 1 M propranolol to eliminate any effect of norepinephrine on ␤-adrenoceptors, another more likely explanation may exist. Cheah et al (8) reported an electrical field stimulation/Ni 2ϩ / Mg 2ϩ -induced vasorelaxation in precontracted endotheliumdenuded rat aortic rings and vasorelaxation mediated through activation of nNOS in the vascular smooth muscle cells. Data from other studies also indicate the existence of nNOS in vascular smooth muscle cells (6,12).…”
Section: Norepinephrine Contraction During Hbo Exposurementioning
confidence: 99%